Mother-father resource control, marriage payments, and girl-boy health in rural Bangladesh - Hallman, Kelly (International Food Policy Research Institute, 2000)
The approach of this study is to examine the effects of household asset ownership patterns on the morbidity status of male and female preschoolers, measured as the number of illness days in the two weeks preceding the household survey.Section 2 of this study outlines the theoretical model. Section 3 describes the data and variables. Section 4 lays out the empirical specification. Sections 5 and 6 present the results and concluding remarks.